2019
DOI: 10.1248/bpb.b19-00385
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Association between Circulating Vitamin D<sub>3</sub> Levels and Clinical Outcomes in Patients with Asthma and Chronic Obstructive Pulmonary Disease: A Prospective Observational Study

Abstract: Vitamin D has an immune-modulating effect, related to the pathophysiology of asthma and chronic obstructive pulmonary disease (COPD). However, few studies have focused on the difference between patients with asthma and COPD in the association of circulating vitamin D levels with clinical outcomes. We sought to investigate the associations of circulating vitamin D levels with health-related QOL (HR-QOL), severity, and exacerbations. Subjects included 152 asthma patients and 50 COPD patients. We measured plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…proposed that severely low 25(OH)D levels (<10 ng/mL) in male patients with COPD can increase the severity and progression of emphysema [19]. Acute exacerbation's timings and frequency were also observed to be increased under the effect of this deficiency in some studies [20,11,4], and some showed the opposite results [10]. When studied in hospitalized or chronically ill populations, an increased rate of deaths was seen among obstructive lung disease populations with severe Vitamin D deficiency, making it a poor prognostic factor with increased mortality rate and poor disease outcome [21][22][23][24].…”
Section: Relationship Between Vitamin D and Copdmentioning
confidence: 99%
“…proposed that severely low 25(OH)D levels (<10 ng/mL) in male patients with COPD can increase the severity and progression of emphysema [19]. Acute exacerbation's timings and frequency were also observed to be increased under the effect of this deficiency in some studies [20,11,4], and some showed the opposite results [10]. When studied in hospitalized or chronically ill populations, an increased rate of deaths was seen among obstructive lung disease populations with severe Vitamin D deficiency, making it a poor prognostic factor with increased mortality rate and poor disease outcome [21][22][23][24].…”
Section: Relationship Between Vitamin D and Copdmentioning
confidence: 99%